Quantum Phase Transition as a Promising Route to Enhance the Critical Current in Kagome Superconductor CsV3Sb5 - Wenyan Wang; Lingfei Wang; Xinyou Liu; Chun Wai Tsang; Zheyu Wang; Tsz Fung Poon; Shanmin Wang; Kwing To Lai; Wei Zhang; Jeffery L. Tallon; Swee K. Goh (Advanced Science)
Abstract Developing strategies to systematically increase the critical current, the threshold current below which the superconductivity exists, is an important goal of materials science. Here, the concept of quantum phase transition is employed to enhance the critical current of a kagome superconductor CsV3Sb5, which exhibits a charge density wave (CDW) and superconductivity that are both affected by hydrostatic pressure. As the CDW phase is rapidly suppressed under pressure, a large enhancement in the self‐field critical current (Ic, sf) is recorded. The observation of a peak‐like enhancement of Ic, sf at the zero‐temperature limit (Ic, sf(0)) centered at p* ≈ 20 kbar, the same pressure where the CDW phase transition vanishes, further provides strong evidence of a zero‐temperature quantum anomaly in this class of pressure‐tuned superconductor. Such a peak in Ic, sf(0) resembles the findings in other well‐established quantum‐critical superconductors, hinting at the presence of enhanced quantum fluctuations associated with the CDW phase in CsV3Sb5.